Age and lesion-induced increases of GDNF transgene expression in brain following intracerebral injections of DNA nanoparticles. (22nd January 2015) - Yurek, D.M.; Hasselrot, U.; Cass, W.A.; Sesenoglu-Laird, O.; Padegimas, L.; Cooper, M.J.
Highlights: Transgene expression in brain is sensitive to aging and pathology. Transgene expression in astrocytes increases directly with age and severity of neurodegeneration. Transfection potential of DNPs is well matched to the pathophysiology of neurodegenerative disorders in aging brain. Abstract: In previous studies that used compacted DNA nanoparticles (DNP) to transfect cells in the brain, we observed higher transgene expression in the denervated striatum when compared to transgene expression in the intact striatum. We also observed that long-term transgene expression occurred in astrocytes as well as neurons. Based on these findings, we hypothesized that the higher transgene expression observed in the denervated striatum may be a function of increased gliosis. Several aging studies have also reported an increase of gliosis as a function of normal aging. In this study we used DNPs that encoded for human glial cell line-derived neurotrophic factor (hGDNF) and either a non-specific human polyubiquitin C ( UbC ) or an astrocyte-specific human glial fibrillary acidic protein ( GFAP ) promoter. The DNPs were injected intracerebrally into the denervated or intact striatum of young, middle-aged or aged rats, and glial cell line-derived neurotrophic factor (GDNF) transgene expression was subsequently quantified in brain tissue samples. The results of our studies confirmed our earlier finding that transgene expression was higher in the denervated striatum when compared to intact striatum for DNPs incorporating either promoter. In addition, we observed significantly higher transgene expression in the denervated striatum of old rats when compared to young rats following injections of both types of DNPs. Stereological analysis of GFAP + cells in the striatum confirmed an increase of GFAP + cells in the denervated striatum when compared to the intact striatum and also an age-related increase; importantly, increases in GFAP + cells closely matched the increases in GDNF transgene levels. Thus neurodegeneration and aging may lay a foundation that is actually beneficial for this particular type of gene therapy while other gene therapy techniques that target neurons are actually targeting cells that are decreasing as the disease progresses.